Comparison of different GPS's used in different areas in our country's forestry - ERDEM, Ramazan; ERDİN, Kadir (Kastamonu University, 2018)
Aim of study: Terrestrial measurements have an important place in the production of spatial databases for use in forestry activities in Turkey. Terrestrial methods develop in parallel to the advancing technology while the mechanical measuring devices used in the past are replaced by computer-assisted digital measuring devices.Area of study:. The Forestry Faculty area of Istanbul University at the European side of province of Istanbul was determined as study area for the present study.Material and Methods: Global positioning systems (GPS) developed to collect satellite-based spatial data are among the devices derived from this technology. This study explored the possibilities to use this technology for forestry purposes and the performance of hand held Global Positioning System, Differential Global Positioning System (DGPS), DGPS-Continuously Operating Reference Stations (CORS) and Total Station on the areas representing the very closed forest area, open area and forest boundary selected for the study was assessed.Main results: According to the results, DGPS CORS type GPS is the most accurate one for all three areas types. It was most accurate in closed forest area as the error margin in dense foliage was 3,41 m in horizontal and 3,88 m in vertical; 0,06 m in horizontal and 0,05 m in vertical for open area; 0,62 m in horizontal and 1,16 m in vertical for forest boundary.Research highlights: It is predicted that DGPS CORS systems to be preferred in forestry operations requiring high sensitivity, whereas usage of hand held GPS systems for time saving.
Keywords: 13. Climate action; 15. Life on land; 7. Clean energy